Husband's Support for Mental Health in Post-Maternal Mothers - Istiana, Siti; Cahyati, Widya Hary (Journal of Creativity Student, 2025)
The postpartum period is a critical transition period for mothers, babies and families both psychologically, emotionally and socially. In the postpartum period, 85% of mothers experienced psychological disorders that showed more significant symptoms. Mental health disorders experienced by mothers will have a direct impact on maternal health and cause postpartum complications. This study was to determine the relationship between husband's support and mental health in postpartum mothers at PMB Tri Utami, Semarang City. The research method used is a survey method with a quantitative type of research. The data collected were analyzed univariately and bivariately using the chi square test. Results: the study based on mental health from 30 respondents found 26 respondents (86.7%) with no symptoms of depression, 4 respondents (13.3%) had symptoms of depression. The results of the Chi Square test obtained a sig value of 0.032 <0.05, which means there is a relationship between husband's support and mental health in postpartum mothers. Conclusion: in the study there is a relationship between husband's support and mental health in postpartum mothers at PMB Tri Utami, Semarang City. The suggestions in this research are expected for midwives to increase attention in providing education to husband and wife couples and families about the importance of support and their role in supporting the mental health of postpartum mothers, so that couples and families can better understand their role in supporting the mental health of mothers throughout the period postpartum.